Diffusion of innovations in the international instrument market. : Case Tonal Innovation Center. - Ruotsalainen, Mikko (fi=Turun yliopisto|en=University of Turku|, 2017)
The slowly declining supply of certain traditional tonewoods together with stricter regulatory measures taken in order to enforce the preservation of these wood species in both the EU and the U.S. have increased the attention around alternative instrument building materials among guitar manufacturers. It is therefore interesting to examine how these changes have affected this relatively traditional industry and if alternative materials are finally starting to shift towards the mainstream. The case organization, Tonal Innovation Center, and its innovative application of natural fiber composite as a new kind of material for building musical instruments, aims to provide a solution for the declining quality of certain tonewoods and replace them with an alternative material that has superior tonal qualities compared to previously introduced alternatives such as carbon fiber, phenolics, high-pressure laminates and the like. The purpose of this case study is to understand and map the diffusion potential of natural fiber composite as an instrument building material in the international musical instrument industry, and especially the international guitar industry. The research aims at studying which factors affect the diffusion of innovations in the international musical instrument market, and it utilizes both a theoretical framework as well as a case study to get there. The theoretical framework of this study is based mainly on Everett M. Rogers’ diffusion of innovations –theory, and it examines the factors that affect the innovation’s diffusion within three points of view: the innovation itself, the business-to-consumer market and the business-to-business market. The empirical data was gathered through semi-structured theme interviews mainly with guitar manufacturers and guitarists, but included also luthiers, music institutes, musical instrument retailers, trade show organizations, as well as material and component suppliers. The research was conducted in three locations: Finland, Germany and the U.S. The guitar market is very traditional when it comes to instruments building materials. However, several large manufacturers have already introduced guitar models with alternative materials in the market, and because of the slowly declining supply of high-quality tonewood, many manufacturers saw the shift towards alternative materials only getting stronger in the future. The manufacturers also saw the need for better alternative materials. Consumer drivers are a big factor in getting alternative materials accepted, and guitarists’ attitudes are already changing for the better as more guitar models with alternative materials are launched in the market. Still, many manufacturers saw the need for education in order to accelerate this change in guitarists’ attitudes.